Deskripsi Disposisi Matematis Mahasiswa Ditinjau dari Perbedaan Gender - Aisyah Nursyam (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2019)
Description of Student Mathematical Disposition Judging from Gender DifferencesÂ This type of research is a descriptive qualitative research. Data obtained by observing and interviewing. The research instrument used was the student interview guide. The purpose of this study is to describe the mathematical disposition of students in terms of gender differences in the fifth semester of the academic year 2019/2020. The subjects of this study were students in group 1 of Semester Lima STKIP Muhammadiyah Bone in the academic year 2019/2020. The results of the study show the indicators of student mathematical disposition that are visible, namely interest and curiosity, confidence, perseverance, and flexibility. The data analysis technique uses three stages, namely reduction, presentation, and drawing conclusions.Â AbstrakÂ Jenis penelitian ini adalah penelitian kualitatif berbentuk deskriptif. Data diperoleh dengan melakukan observasi dan wawancara. Instrumen penelitian yang dipakai adalah pedoman wawancara mahassiswa. Tujuan dalam penelitian ini yaitu untuk mendeskripsikan disposisi matematis mahasiswa ditinjau dari perbedaan gender semester lima tahun ajaran 2019/2020. Subjek penelitian ini adalah siswa kelompok 1 Semester Lima STKIP Muhammadiyah Bone tahun pelajaran 2019/2020. Hasil penelitian menunjukan indikator disposisi matematis mahasiswa yang terlihat yaitu minat dan rasa ingin tahu, percaya diri, tekun, dan fleksibel. Teknik analisis data menggunakan tiga tahapan, yaitu reduksi, penyajian, dan penarikan kesimpulan.